High-Frequency Plant Regeneration, Genetic Uniformity, and Flow Cytometric Analysis of Regenerants in Rutachalepensis L. - Ahmed A. Qahtan; Mohamad Faisal; Abdulrahman A. Alatar; Eslam M. Abdel-Salam (Plants, 2021)
Ruta chalepensis L., an evergreen shrub in the citrus family, is well-known around the world for its essential oils and variety of bioactivities, indicating its potential medicinal applications. In this study, we investigated the effect of different culture conditions, including plant growth regulators, media types, pH of the medium, and carbon sources, on in vitro regeneration from nodal explants of R. chalepensis. Following 8 weeks of culture, the highest percentage of regeneration (96.3%) and maximum number of shoots (40.3 shoot/explant) with a length of 4.8 cm were obtained with Murashige and Skoog (MS) medium at pH 5.8, supplemented with 3.0% sucrose and 5.0 µM 6-Benzyladenine (BA) in combination with 1.0 µM 1-naphthaleneacetic acid (NAA). For rooting, individually harvested shootlets were transferred on ½ MS (half-strength) supplemented with IAA (indole-3-acetic acid), IBA (indole 3-butyric acid), or NAA, and the best response in terms of root induction (91.6%), number of roots (5.3), and root mean length (4.9 cm) was achieved with 0.5 µM IBA after 6 weeks. An average of 95.2 percent of healthy, in vitro regenerated plantlets survived after being transplanted into potting soil, indicating that they were effectively hardened. DNA assays (PCR-based markers) such as random amplification of polymorphic DNA (RAPD) and directed amplification of minisatellite-region (DAMD) were employed to assess in vitro cultivated R. chalepensis plantlets that produced a monomorphic banding pattern confirming the genetic stability. Additionally, no changes in the flow cytometric profile of ploidy between regenerated plantlets and donor plants were detected. Regeneration of this valuable medicinal plant in vitro will open up new avenues in pharmaceutical biotechnology by providing an unconventional steadfast system for mass multiplication and might be effectively used in genetic manipulation for enhanced bioactive constituents.